(3CQLhRg aj GdfZeGJ hGdVQhH GdehSjbjI hTQMgGs - (3eMeO Hf eMeO Hf CMeO GdPgHjs
(3ChdgG (B:s
(3hHYO aEfi deG eGQSJ Yde GdehSjbG hGJbafJg YdekG hYedkG s
(3BNQgG (B:s
(3hgPg GdaGFOI Ydi JQJjH GdCfZGe dGYdi JQJjH GdHQhL s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B506) s
Keywords: (3GdehSjbi hGdZfGAs